Supercritical-pressure light water cooled reactors - Mori, Hideo; Oka, Yoshiaki (Springer Japan, 2014)
This book focuses on the latest reactor concepts, single pass core and experimental findings in thermal hydraulics, materials, corrosion, and water chemistry. It highlights research on supercritical-pressure light water cooled reactors (SCWRs), one of the Generation IV reactors that are studied around the world. This book includes cladding material development and experimental findings on heat transfer, corrosion, and water chemistry. The work presented here will help readers to understand the fundamental elements of reactor design and analysis methods, thermal hydraulics, materials, and water chemistry of supercritical water used as a coolant in nuclear power reactors. It will also help readers to broaden their understanding of fundamental elements of light water cooled reactor technologies and the evolution of reactor concepts.